IS LONG-RUN MONETARY NEUTRAL? EVIDENCE FROM INDONESIA - Arintoko Arintoko (Universitas Islam Indonesia, 2009)
This paper examines the long-run monetary neutrality in Indonesia, mainly using annual time-series during 1970-2007. It uses Fisher-Seater methodology to analyze the research problems. Particular attention is given to integration, exogeneity, and cointegration properties of the money stock and real output. Unit-root, causality, and cointegration tests are used to identify these properties. The empirical results provide evidence to reject the long-run neutrality of money (both M1 and M2) with respect to real GDP, showing that it is inconsistent with the classical and neoclassical economics. In particular, government injections of money have long-run positive effect on real output in macroeconomy.